GeoGebra: Transformasi Teknologi yang Menyulap Pembelajaran Matematika Menjadi Lebih Menyenangkan - Gusteti, Meria; Rahmalina, Widdya; Azmi, Khairul; Wulandari, Suci; Mulyati, Asrina; Hayati, Rahmatul; Wahyuni, Zelfi; AlFath, Muhammad Ro’id; Azizah, Nur (Lembaga Dongan Dosen, 2023)
Mathematics learning is often perceived as monotonous and challenging to comprehend. This community service aims to introduce GeoGebra as a technological transformation that can make the mathematics learning process more engaging. Through a questionnaire approach filled out by students, it was found that the majority of participants felt more interested and motivated to learn mathematics with GeoGebra. They acknowledged gaining a deeper understanding of mathematical concepts and felt more confident in solving problems. Moreover, GeoGebra offers a new perspective on mathematics and encourages independent learning. In conclusion, GeoGebra holds significant potential in altering students' perceptions of mathematics, making it appear more enjoyable and understandable